The Role of Teachers in Promoting Play-Based Learning in STEAM Education in Early Childhood Education - Mwariko, Sadick Akida; Kurniati, Euis (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2024)
In recent years years, play-based learning (PBL) has gained attention as an effective approach to early childhood education, especially in STEAM. Play-based learning can be an effective way to introduce young children to science, technology, engineering, art, and mathematics concepts in a very fun and engaging way. Teachers play a vital role in promoting PBL in early STEAM education by creating a classroom environment that encourages exploration, experimentation, and collaboration skills. However, the limited research on the roles of teachers in promoting play-based learning in STEAM in early childhood education (ECE) drives the author to conduct this study to provide insight into how teachers can engage constructively to promote PBL in STEAM in early childhood education. This study aims to address this gap by exploring the role of teachers in promoting PBL in early STEAM education. Through a literature review, the paper defines PBL and STEAM, emphasizing the importance of PBL for young children's development. It also discusses the significance of teacher training and professional development in enhancing their ability to support PBL. Lastly, identifies challenges and opportunities in implementing PBL in STEAM, offering recommendations for future research to better integrate these practices in early childhood education.